2004
DOI: 10.1016/j.nuclcard.2004.06.128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of risk stratification with pharmacologic and exercise stress myocardial perfusion imaging: A meta-analysis

Abstract: This meta-analysis shows that exercise stress MPI and pharmacologic stress MPI are comparable in their ability to risk-stratify patients. However, patients undergoing pharmacologic stress studies are at a higher risk for subsequent cardiac events. This is true even for those with normal perfusion imaging results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
102
1
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(127 citation statements)
references
References 51 publications
14
102
1
10
Order By: Relevance
“…In agreement with the literature, we found a higher rate of adverse heart events in the group of patients who were submitted to pharmacological stress both for patients with normal tests and for those with altered tests 33,34 . We believe that this was due to the fact that the population submitted to pharmacological stress was comprised of patients with more severe cardiac disease than the population submitted to physical stress.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the literature, we found a higher rate of adverse heart events in the group of patients who were submitted to pharmacological stress both for patients with normal tests and for those with altered tests 33,34 . We believe that this was due to the fact that the population submitted to pharmacological stress was comprised of patients with more severe cardiac disease than the population submitted to physical stress.…”
Section: Discussionsupporting
confidence: 92%
“…Navarre et al reported an annual hard event rate of 10.9% for pharmacologic MPI patients with severe perfusion defects, compared to 6.4% for exercise MPI patients with severe defects. 5 Similar findings were reported by Hachamovitch et al in elderly patients. 6 The annualized cardiac mortality was 7.8% for patients with moderately abnormal MPI results with pharmacologic stress vs 2.7% with such abnormal results in patients who underwent exercise MPI.…”
supporting
confidence: 84%
“…However, patients undergoing pharmacologic stress studies tend to be a sicker group by the fact that they are not able to exercise, and are at a higher risk for subsequent cardiac events, even when the MPI test is normal. 7 Rozanski et al reported similar findings among patients tested with exercise or adenosine stress protocol. 8 Dakik et al also reported that, in spite of the decline in the rate of abnormal or ischemic MPI that has been reported in the USA and in the Middle East region over the last two decades, the rates of ischemia at the American University of Beirut Medical Center remain relatively high.…”
mentioning
confidence: 70%